Odpowiedź :
5x-2x=8+4
3x=12/:3
x=4
2x+5x-4x=3
3x=3/:3
x=3
8x-7=2x+10
8x-2x=10+7
6x=17/:6
x=17/6=2 5/6
mam nadzieję że pomogłam, pozdrawiam
Szczegółowe wyjaśnienie:
5x -4 = 2x +8
5x - 2x = 8 + 4
3x = 12 /:3
x = 4
spr.
5×4 - 4 = 2 × 4 + 8
20 - 4 = 8 + 8
16 = 16
L = P
2x + 5x -3 = 4x
2x + 5x - 4x = 3
3x = 3 /:3
x = 1
spr.
2×1 + 5× 1 - 3 = 4× 1
2 + 5 - 3 = 4
7 - 3 = 4
L = P
8x - 7 = 2x + 10
8x - 2x = 10 + 7
6x = 17 /:6
x = 17/6
spr.
8/1 × 17/6 - 7 = 2/1 × 17/6 +10
136/6 - 42/6= 34/6 + 60/6
94/6 = 94 /6
15 4/6 = 15 4/6
15 2/3 = 15 2/3
L = P